Reliability of an Integrated Ultrasound and Stereophotogrammetric System for Lower Limb Anatomical Characterisation - Frederick Greatrex; Erica Montefiori; Thomas Grupp; Josef Kozak; Claudia Mazzà (Applied Bionics and Biomechanics)
Background. Lower extremity analysis for preoperative total knee and hip arthroplasty routines can increase surgery success rate and hence reduce associated costs. Current tools are limited by being invasive, limited to supine analysis, or too expensive. This study aimed to propose and validate a device, OrthoPilot®, based on the combined use of a stereophotogrammetric and ultrasound system which can in vivo and noninvasively measure varus/valgus, flexion/extension, femur and tibia torsion, and femur and tibia lengths. Methods. A phantom was measured by four operators to determine the resolution of the system. Interoperator variability was measured on three operators who measured the above six variables on both legs of three subjects in standing and supine positions. Intraoperator variability was assessed on data from three repeats from 9 subjects (18 legs). Results. All 6 variables were reliably detected on a phantom, with a resolution of 1 mm and 0.5°. Inter- and intraoperator consistency was observed for varus/valgus, flexion/extension, and length measurements on the healthy subjects in standing and supine positions (all ICC > 0.93). For torsion measurements, there was a considerable variation. Conclusion. The proposed system, when used on healthy subjects, allowed reliable measurements of key parameters for preoperative procedures in both supine and standing positions. Accuracy testing and further validation on patient populations will be the next step toward its clinical adoption.